BIG DATA: THE UBIQUITOUS DATA THAT ORGANIZATIONS NEED TO LEVERAGE NOWADAYS - Alexandra, PRICOP G.; Gheorghe, ORZAN (Annales Universitatis Apulensis Series Oeconomica, 2018)
Information is modeling each aspect of everyday life: the personal environment, the cultural, religious, social, political and economic environments. The innovations in technology provide a wide distribution of ideas, thoughts, decisions, behaviors, facts and events, which enlarge the traditional data field, overpassing the processing capacity of standard analysis devices and the use of conventional analysis models and defining the ‘Big Data’ concept. This paper provides an understanding of Big Data from an economic standpoint and proposes five areas to focus on when leveraging Big Data: transparency, test environment, real-time decision-making, management augmentation and prediction of the future trends.